Experimental Investigations on Mechanical Properties of Consolidated Samples for Collapse Columns under Seepage-Stress Coupling Effects - Yanhui Du; Dawei Yin; Shijian Yu; Hongyang Liu; Weitao Liu; Xiangkai Zhang (Lithosphere, 2022)
AbstractTriaxial seepage tests were conducted on the consolidated collapse column specimens to investigate their mechanical properties under seepage-stress coupling effects using a triaxial multifield coupled mechanical test system for rocks. The effects of initial consolidation pressures and specimen components on mechanical properties and seepage characteristics of consolidated collapse column specimens were analyzed. Test results showed the following: (1) The stress–strain curves of consolidated collapse column specimens could be classified in three stages, namely, compaction stage, linear deformation stage, and creep-like deformation stage, while the permeability during loading showed an obvious four-stage evolution of gradual decrease, stable development, rapid increase, and slow decrease. (2) Under same sample components, the permeability characteristics of consolidated collapse column specimens showed an obvious initial consolidation pressure effect. The initial consolidation pressure changed the distribution of pores and fractures in the specimens, leading to a decreased peak permeability as the initial consolidation pressure increased. (3) At the initial stage of loading, the permeability of consolidated specimens was mainly affected by the initial consolidation pressure, and the corresponding permeability decreased with the increase of the consolidation pressure. When the consolidated specimens were gradually compacted, the main factor influencing the permeability changed to the specimen components. The peak permeability of consolidated specimens comprising grey mudstone and conglomerate was the largest, while the fuchsia mudstone would reduce the specimen permeability, and the peak permeability decreased with the fuchsia mudstone components.